UMPSA lecturers participate in the 2024 Technology Carnival CSR Programme - Asnul Hadi, Ahmad (UMPSA, 2024)
KUALA LIPIS, 13 June 2024 – Lecturers and students of the Faculty of Mechanical and Automotive Engineering Technology (FTKMA) at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) participated in the Corporate Social Responsibility (CSR) Programme of Technology Carnival 2024 at Sekolah Menengah Kebangsaan RPS Betau, Kuala Lipis.